(untitled) (Italian Journal of Public Health, 2005)
The Authors examine the global, European and Italian epidemiology of HIV/AIDS on the basis of more recent international and national reports. All limitations in the available data were considered. The epidemic seems to have expand in all of the areas, demonstrating the need for further interventions both in the prevention of the infection and the diffusion of antiretroviral treatments, where these are lacking